Alleviation of Neuropathic Scar Pain Using Autologous Fat Grafting. (May 2015) - Huang, Shu-Hung; Wu, Sheng-Hua; Chang, Kao-Ping; Lin, Cen-Hung; Chang, Chih-Hau; Wu, Yi-Chia; Lee, Su-Shin; Lin, Sin-Daw; Lai, Chung-Sheng
Abstract : Abstract: Traumatic wounds inflict small- and large-fiber sensory nerve damage, causing neuropathic pain in scar tissue, thus impairing patients' quality of life and leading to the development of psychological disorders. Autologous fat grafting has been clinically shown to improve scar quality, but few studies have explored the effects of this technique on pain. The purpose of this study was to assess the effect of fat grafting on treating neuropathic scar pain. From February 2008 to January 2013, 13 patients who were identified using the Douleur Neuropathique 4 Questions (scores >4/10) were enrolled in this study. The Visual Analog Scale (VAS) and Neuropathic Pain Symptom Inventory (NPSI) were used to evaluate pain preoperatively and 1 week, 4 weeks, and 24 weeks postoperatively. The mechanism of trauma, scar location and size, duration of allodynia, fat graft volume, pharmacologic therapy duration, and total follow-up time were recorded. Thirteen patients experiencing neuropathic pain were enrolled in this study. The mean ± SD age was 33.08 ± 16.35 years. The mean duration of pain was 4.29 ± 2.85 months. The mean VAS score before treatment was 7.54 ± 1.05. The mean VAS scores decreased by 4.38 ± 1.66 after 1 week of treatment ( P = 0.009), 5.38 ± 2.06 after 4 weeks of treatment, and 5.62 ± 2.18 after 24 weeks of treatment. The mean NPSI scores were 49.38 ± 13.25 before treatment, 25 ± 14.4 after 1 week of treatment ( P = 0.004), 21 ± 17.78 after 4 weeks of treatment, and 14.62 ± 16.88 after 24 weeks of treatment. The 13 patients followed a mean of 24 weeks; 10 (77%) of the patients had improvement of 5 or greater on the VAS score. The mean follow-up period was 19.3 ± 12.26 months (range, 6–38 months). No surgical complications were noted in this series. In our study, both VAS and NPSI scores decreased significantly, revealing that the autologous fat grafting can alleviate neuropathic scar pain 1 week after operation and in the long term. Abstract : Supplemental digital content is available in the text.